2019
DOI: 10.1111/nep.13207
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin use and the risk of stroke, bleeding, and mortality in older adults on dialysis with incident atrial fibrillation

Abstract: Older ESRD patients with AF who were treated with warfarin had a no difference in stroke risk, lower mortality risk, but increased major bleeding risk. The bleeding risk associated with warfarin was greater among women than men. The risk/benefit ratio of warfarin may be less favorable among older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 50 publications
(126 reference statements)
2
34
0
3
Order By: Relevance
“…The subgroup analysis revealed a significant association of warfarin use with the intracranial hemorrhage/hemorrhagic stroke (nine studies; pooled RR: 1.43 [95% CI: 1.20–1.71, P = < 0.0001]) . In contrast, no significant association was observed between warfarin use and risk of gastrointestinal bleeding (seven studies; pooled RR: 1.69 [95% CI: 0.74–3.83, P = 0.21]) . The subgroup analysis based on study design and study quality also demonstrated a significant association in our study.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…The subgroup analysis revealed a significant association of warfarin use with the intracranial hemorrhage/hemorrhagic stroke (nine studies; pooled RR: 1.43 [95% CI: 1.20–1.71, P = < 0.0001]) . In contrast, no significant association was observed between warfarin use and risk of gastrointestinal bleeding (seven studies; pooled RR: 1.69 [95% CI: 0.74–3.83, P = 0.21]) . The subgroup analysis based on study design and study quality also demonstrated a significant association in our study.…”
Section: Resultssupporting
confidence: 48%
“…using US Renal Data System. So, the study with most detailed information was included in the meta‐analysis . A detailed description of article selection process was shown using Preferred Reporting Items for Systematic Review and Meta‐analysis diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, approximately 795 000 people have a stroke each year . Patients with end‐stage renal disease (ESRD) are not only at higher risk for stroke but also have higher poststroke mortality . In addition to traditional risk factors for cardiovascular disease, specific risk factors related to ESRD such as the use of erythropoiesis‐stimulating agent and systemic inflammation may play an important role as well …”
Section: Introductionmentioning
confidence: 99%
“…2 Patients with end-stage renal disease (ESRD) are not only at higher risk for stroke [6][7][8] but also have higher poststroke mortality. 7,9 In addition to traditional risk factors for cardiovascular disease, specific risk factors related to ESRD such as the use of erythropoiesis-stimulating agent and systemic inflammation may play an important role as well. [10][11][12][13] c 2018 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd It is unclear whether the choice of dialysis modality affects the risk of stroke.…”
Section: Introductionmentioning
confidence: 99%